2022
DOI: 10.1111/opo.13023
|View full text |Cite
|
Sign up to set email alerts
|

Association between axial length elongation and spherical equivalent progression in Chinese children and adolescents

Abstract: Background It is generally believed that a 1‐mm axial length (AL) elongation of the eye corresponds to a −3.00 D spherical equivalent (SE) progression, but this is disputed. Purpose To investigate the association between AL elongation and SE progression among children and adolescents. Methods A prospective cohort study of 710 children and adolescents aged 6–16 years was included. Ophthalmic examinations, including cycloplegic SE, AL and corneal curvature, were performed at baseline and 1‐year follow‐up. The ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
2
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 45 publications
(87 reference statements)
2
2
1
Order By: Relevance
“…The present study focused on preschoool children under the age of 6, so ∆SE/∆AL was relatively lower compared to the results of the study conducted on school children. This finding is consistent with a previous study on myopia, where a 1 mm increase in AL corresponded to more myopic progression in SE for older children 18 .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The present study focused on preschoool children under the age of 6, so ∆SE/∆AL was relatively lower compared to the results of the study conducted on school children. This finding is consistent with a previous study on myopia, where a 1 mm increase in AL corresponded to more myopic progression in SE for older children 18 .…”
Section: Discussionsupporting
confidence: 93%
“…Our study showed gradually decreased myopic progression and axial elongation over 3-year study period, which was like previous studies 16 , 18 . The previous study reported that AL elongation decreased to the order of 0.14 mm/year from 3 to 6 years of age 14 .…”
Section: Discussionsupporting
confidence: 91%
“…Some children did not have cycloplegic refraction in the follow-up tests, and the results might overestimate the progression of myopia. However, we found a corresponding axial elongation associated with SER progression in children 25 . In addition, the data were from Chinese children in only one region.…”
Section: Limitations Of the Studycontrasting
confidence: 47%
“…Axial shortening >0.25 mm/year (i.e., progression <−0.25 mm/year) was removed as outliers given that no anti‐myopia product was used. Additionally, the following filters were applied: age range of 6.0–16.9 years, spherical equivalent RE −6.00 to +6.00 D, outliers above the 99.5 percentile (1%), outside the 3 × standard deviation (SD) boundary limits applied to the linear relationship of spherical equivalent progression versus axial elongation 26 (2.4%) and missing progression data (5%). Finally, 91.6% of the sample was retained.…”
Section: Methodsmentioning
confidence: 99%